Perforated duodenal ulcer: an unusual complication of meningitis - Tanzer, Fatoş; Baskın, Esra; İçli, Fevzi and Toksoy, Hayri and Gökalp, Ayşe (The Turkish Journal of Pediatrics, 1994)
An 11-month-old boy was admitted to the hospital with fever, vomiting and seizures and was diagnosed with purulent meningitis. Two days later, an acute, perforated, duodenal ulcer was detected in the patient. Surgery was performed, and the patient made an uncomplicated recovery. Peptic ulceration is underdiagnosed in children and this leads to delay in diagnosis and appropriate management. Peptic ulceration may occur during severe illness or viral infections, but perforation is rare.